Serotype distrubution and antibiotic susceptibilities of streptococcus pneumoniae causing acute exacerbations and pneumonia in children with chronic respiratory diseases [Kronik akciǧer hastaliǧi olan, akut alevlenme ve pnömoni tanisi ile başvuran çocuklarda streptococcus pneumoniae serotip daǧilimi ve antimikrobiyal duyarliliklari] - KARADAĞ, BÜLENT TANER; ALTINKANAT GELMEZ, GÜLŞEN; HASDEMİR GÖKBOĞA, MÜNEVVER UFUK (Ankara Microbiology Society, 2013)
This study aimed to investigate serotype distribution and antimicrobial resistance of Streptococcus pneumoniae isolates obtained from children with chronic respiratory diseases admitted to hospital with a diagnosis of acute exacerbations between 2008-2010 at Marmara University Hospital, Istanbul, Turkey. Sixty one S.pneumoniae strains isolated from the respiratory samples of patients were studied for erythromycin, clindamycin, tetracyline, trimethoprim-sulphametoxazole (TMP-SMX), vancomycin, levofloxa-cin susceptibilities by disk diffusion method; MIC values of penicillin and ceftriaxone were determined by E-test (AB Biodisk, Sweden). Results were evaluated according to the CLSI standards. The erythromycin-clindamycin double disc method was applied for the detection of macrolide resistance phenotypes. The presence of macrolide resistance genes, ermB, mef(A)/(E), ermTR were determined by PCR using specific primers for each gene. The serotypes were determined by multiplex PCR using specific primers for 40 different serotypes. According to CLSI criteria, penicillin resistance in S.pneumoniae isolates were found to be 8.2% (5/61) and intermediate resistance rate was 54% (33/61) for oral penicillin. Penicillin resistance were found to be only 1.6% (1/61) for parenteral penicillin. Resistance rates of erythromycin, clindamycin, tetracyline, TMP-SMX were detected as 55.8%, 46%, 47.5% and 67.2%; respectively. No resistance was detected to vancomycin and levofloxacin. Constitutive macrolide-lincosamide-streptog-ramin B (cMLSB) phenotype and M phenotype were observed in 82.4% (n= 28) and 17.6% (n= 6) of the macrolide resistant isolates, respectively. Inducible macrolide-lincosamide-streptogramin B (iMLSg) phenotype was not detected. The macrolid resistance genotypes, ermB, mef(A)/(E), were positive 50% and 14.7%; respectively. Both ermB and mef(A)/(E) genes were detected 35.3% of the macrolid resistant isolates. None of the isolates were positive for ermTR gene. The most common S.pneumoniae serotypes were determined as serotype 19F, 23F and 6, furthermore penicillin (34%, 15.7% and 18.4%, respectively) and macrolide (38.2%, 20.6% and 14.7%, respectively) resistance rates of those serotypes were found relatively high. Serotype covarage of 7-, 10-, 13-valent conjugated pneumococcal vaccines and 23-valent pneumococcal vaccine were 65%, 67%, 69%, and 78.6%, respectively. In our country, use of the vaccines with these coverage rates has been observed to be effective in children exposed to intensive use of antibiotics with chronic lung disease.
Keywords: Antibiotic susceptibility; Chronic respiratory disease; Serotyping; Streptococcus pneumoniae